Effect of climate area on yield and quality of three varieties of Megathyrsus maximus - Méndez, Y.; Reyes, J. J.; Luna, R. A.; Verdecia, D. M.; Espinoza, A. L.; Pincay, W. J.; Espinosa, K. A.; Macías, R. K.; Herrera, R. S. (Cuban Journal of Agricultural Science, 2020)
The effect of climatic area (Guayas and El Empalme) on quality indicators of three varieties of Megathyrsus maximus (Common, Tanzania and Tobiatá) was studied using a random block design with factorial arrangement (3x2). Yields of total dry matter, biomass, leaves and stems were determined, as well as height of the plant, length and width of leaves. Contents of DM, CP, NDF, ADF, ADL, cellulose (CEL), hemicellulose (HCEL), cellular content (CC), P, Ca, ash, OM, DMD, OMD, ME, NFE and leaf-stem, NDF/N and ADF/N relationships. There was a significant interaction (P <0.0001) between varieties and area, for some of the studied indicators. The highest DM and biomass yields were obtained in Tanzania in El Empalme (2.17 and 6.97 t / ha, respectively, P <0.0001), and those of PB were for Tanzania in Guayas (12.52%, P <0.0001), while cell wall components did not differ among varieties, only ADL was significant for Guayas (3.82 %, P <0.004). The effect of climatic area on yield and quality of forages was demonstrated in the current research, where the best performance of productivity and morphological development was obtained in the area with the highest rainfall (El Empalme), while quality was better for that with the lowest rainfall (Guayas). Although there were no differences for leaf growth, cell wall components, digestibility and energy contribution, its adaptability and potential in the different ecosystems are confirmed. Key words: biomass, production, region, chemical composition, digestibility, energy